2008
DOI: 10.1007/s10545-007-0716-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between interleukin‐6 promoter and C‐reactive protein (CRP) polymorphisms and CRP levels with the Mainz Severity Score Index for Fabry disease

Abstract: The prevalence of the IL-6 C allele significantly influences MSSI, i.e. clinical severity, especially in females. This is unrelated to IL-6 as a pro-inflammatory marker as demonstrated by lack of correlations with CRP levels and genotypes. IL-6 -174 polymorphic C allele may be a prognostic marker in Fabry disease, especially in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
1
15
0
2
Order By: Relevance
“…The lack of correlation with CRP echoes previous studies where CRP was not associated with the MSSI and clinical severity in Fabry disease (Altarescu et al 2008;Vedder et al 2009). The significant difference in ESR between CVD-positive and CVDnegative patients (23.8 vs. 7.64) and the correlation between ESR and positive CVD history is a novel finding.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The lack of correlation with CRP echoes previous studies where CRP was not associated with the MSSI and clinical severity in Fabry disease (Altarescu et al 2008;Vedder et al 2009). The significant difference in ESR between CVD-positive and CVDnegative patients (23.8 vs. 7.64) and the correlation between ESR and positive CVD history is a novel finding.…”
Section: Discussionsupporting
confidence: 82%
“…These changes are proposed to cause the cerebral tissues to become more metabolically vulnerable leading to demyelination, gliosis, increased interstitial water content and finally to WML formation (Moore et al 2003). Thus, while the exact cellular mechanisms that result in vascular pathology are unknown, a vascular dysfunction is present (Mehta and Ginsberg 2005;Altarescu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors conducted a study [58] that showed that the MSSI score may be a useful, specific measure for objectively assessing the severity of AFD and for monitoring ERT. Fabry disease is a multisystem disorder with phenotypic heterogeneity only partially explained by genotype.…”
Section: Afd As a Multiorgan Disease Potential Ge-netic And Circulatmentioning
confidence: 99%
“…As for other inflammatory cytokines, Altarescu et al investigated the association between IL-6 polymorphism and/ or CRP levels or polymorphism and severity of cardiovascular involvement in Fabry disease; however, the results did not support their hypothesis (20). In 36 Fabry disease patients with renal impairment, markers for coagulation activation, fibrinolysis, platelet activation, endothelial activation and acute phase response (including CRP) were studied.…”
Section: F I G U R E 3 Cl I N I C a L C O U R S E O F Ca S Ementioning
confidence: 99%